2020
DOI: 10.1002/jcb.29614
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1 overexpression in human neuroblastoma cell lines causes cell‐cycle arrest by G1/S checkpoint block

Abstract: Monocyte chemoattractant protein-1-induced protein 1 (MCPIP1) has a multidomain structure, which assures its pleiotropic activity. The physiological functions of this protein include repression of inflammatory processes and the prevention of immune disorders. The influence of MCPIP1 on the cell cycle of cancer cells has not been sufficiently elucidated. A previous study by our group reported that overexpression of MCPIP1 affects the cell viability, inhibits the activation of the phosphoinositide-3 kinase/mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 49 publications
(117 reference statements)
3
22
0
Order By: Relevance
“…In the present study, we elaborate on the mechanisms of MCPIP1 ribonuclease action in MNA neuroblastoma cells. Based on our previous findings [17][18][19], we proposed several putative MCPIP1's substrates in neuroblastoma cells. In order to verify their interaction with the ribonuclease, we demonstrated that the overexpression of MCPIP1 leads to decreased levels of a few mRNAs, encoding proteins facilitating cell cycle progression in a RNase-dependent manner.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In the present study, we elaborate on the mechanisms of MCPIP1 ribonuclease action in MNA neuroblastoma cells. Based on our previous findings [17][18][19], we proposed several putative MCPIP1's substrates in neuroblastoma cells. In order to verify their interaction with the ribonuclease, we demonstrated that the overexpression of MCPIP1 leads to decreased levels of a few mRNAs, encoding proteins facilitating cell cycle progression in a RNase-dependent manner.…”
Section: Introductionmentioning
confidence: 88%
“…The previously used experimental model contained the control for both, the MCPIP1 overexpression (cells transfected with an empty expression vector) and the protein's ribonucleolytic activity (cells overexpressing the mutated form of MCPIP1). Using this model we have shown a broad range of alteration in transcriptome and proteome of neuroblastoma cells overexpressing MCPIP1 protein via application of microarrays, RT-qPCR and western blot [17][18][19]31]. The decreased transcript expression in the cells overexpressing the wild-type form of MCPIP1, and simultaneously, unaltered levels in the cells with overexpression of the mutated form of the protein, points to the indispensability of the ribonucleolytic activity of MCPIP1 for the observed downregulation of a mRNA.…”
Section: Six Transcripts Associated With Cell Cycle Progression Are Pmentioning
confidence: 94%
See 3 more Smart Citations